What is the impact of the global financial crisis on the banking system in East Asia? - Michael Pomerleano (Asian Development Bank Institute (ADBI), 2009)
I analyze the risks in the banking systems in East Asia using the standard supervisory framework, which assesses capital adequacy, asset quality, management, earnings, and liquidity (CAMEL), I find that banking systems in the region are sound, but that the short-term outlook is negative. Second, I review the measures introduced in Asian countries to support their banking systems. The main bank support measures - direct capital support, removal and guarantees of bad assets, direct liquidity support, and guarantees for banks' existing or newly issued obligations - might be necessary to ensure stability, but they need to be handled carefully to prevent long-term distortions. It remains to be seen whether Asian policymakers will manage skillfully the lifting of bank support measures. Third, I conduct stress tests of the banking systems. The stress tests indicate that the largest banking systems in East Asia have a total of almost US1.2 trillion in Tier 1 capital and a possible shortfall of US758 billion. Fourth, I assess the implications for liquidity of the increase in international banking flows and find that the banking system in the Republic of Korea appears vulnerable to a reversal of capital flows. Fifth, I explore the implications of the crisis for credit formation, assessing whether nonbank financial institutions in the region have the capacity to provide sufficient liquidity. I conclude that they do not. The paper ends with a brief assessment of the impact of the crisis on the corporate sector, concluding that the effects of the crisis are likely to be significant but manageable.
Keywords: F37; G15; G2; 330